A Test for the Homogeneity of Mixtures with Varying Concentrations - Maiboroda, R. E. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We construct a generalized version of the Kolmogorov–Smirnov test for the verification of a hypothesis concerning the homogeneity of a sample against an alternative sample from a mixture with varying concentrations. We obtain asymptotic formulas and nonasymptotic upper bounds for the probabilities of errors of the first and second kinds.